Parent escalation of care for the deteriorating child in hospital: A health‐care improvement study - Fenella J. Gill; Gavin D. Leslie; Andrea P. Marshall (Wiley, 2019)
Abstract Objective To evaluate the implementation of an intervention for parents to escalate care if concerned about their child's clinical condition. Design Mixed‐methods health‐care improvement approach guided by the Theoretical Domains Framework. Methods Implementation of the 'Calling for Help' (C4H) intervention was informed by previously identified barriers and facilitators. Evaluation involved audit, review of clinical deterioration incidents, interviews and focus groups. Setting Australian specialist paediatric hospital. Participants Convenience sample of 75 parents from inpatient areas during the audit, interviews with ten parents who had expressed concern about their child's clinical condition; five focus groups with 35 ward nurses. Main outcome measures Parent awareness and utilization of C4H, parent and nurse views of factors influencing implementation. Results Parent awareness of C4H improved to 35% (25/75). Parent concern was documented prior to 21/174 (12%) clinical deterioration events. All interviewed parents and nurses who participated in focus groups were positive about C4H. Parents preferred to be informed about C4H by nurses, but nurses described this as time‐consuming and selectively chose parents who they believed would benefit most. Parents and nurses described frustrations with and trepidation in escalating care. Nurses had used C4H to expedite urgent medical review. Conclusions There was an improvement in the level of parent awareness of C4H, which was viewed positively by parents and nurses alike. To achieve a high level of parent awareness in a sustainable way, a multifaceted approach is required. Further strategies will be required for parents to feel confident enough to use C4H and to address interprofessional communication barriers.